Impact of Net Zero Emission 2060 Initiatives to the Commercial Electric Vehicle Adoption in Indonesia: A System Dynamic Model Approach - Abdu Robbi; Yos Sunitiyoso (Eduvest - Journal of Universal Studies, 2026)
Indonesia has committed to achieving Net Zero Emissions (NZE) by 2060, with transport electrification identified as one of the key mitigation strategies. This study investigates the impact of government policies on commercial electric vehicle adoption, particularly electric buses, in Indonesia using a System Dynamics approach. A simulation model was developed in Vensim® PLE 10.3.1 based on Causal Loop Diagrams (CLDs) and Stock-and-Flow Diagrams (SFDs) to evaluate 17 policy scenarios over the 2026–2060 period. The scenarios represent combinations of value-added tax (VAT) incentives, fuel price reforms, and electricity tariff policies under Indonesia’s Enhanced Nationally Determined Contribution (ENDC). The findings indicate that, under business-as-usual conditions, commercial electric bus adoption remains limited, reaching only approximately 8,925 units by 2060. The Total Cost of Ownership (TCO) is identified as the primary determinant of adoption, with fuel prices exerting the strongest influence on market competitiveness. Among the evaluated scenarios, the combination of a 10% VAT incentive and fuel subsidy removal produces the best outcome, enabling the market to reach the projected saturation level of 132,000 electric buses while expanding domestic manufacturing capacity to more than 20,500 units annually. This scenario is also projected to reduce approximately 8,785 Gg CO₂ emissions in 2060, contributing 18–22% of the annual emissions reduction target under Indonesia’s Second Nationally Determined Contribution (SNDC). The results highlight that fuel price reform is the most effective policy instrument, while VAT incentives and affordable electricity tariffs play complementary roles in accelerating commercial electric vehicle adoption.